Promising Agricultural Management Practices and Soil Threats in Europe and China - Barão, Lúcia (2021)
Advising farmers on the best agricultural management practices (AMP) to be adopted in order to sustain agricultural productivity while improving soil quality is mandatory to assure future food production. Some promising AMPs have been suggested over the time to prevent soil degradation. These practices have been randomly adopted by farmers but which ones are mostly used by farmers and where they have been applied remains unclear. As part of the iSQAPER project—Interactive Soil Quality Assessment in Europe and China for Agricultural Productivity and Environmental Resilience—we (1) mapped the current distribution of previously selected 18 promising AMPs in several pedoclimatic regions and farming systems along Europe and China, based on ten and four study site areas (SSA), respectively; and (2) identified the soil threats occurring in those areas. In each SSA, farmers using promising AMPs were identified and questionnaires were used to assess farmer’s perception on soil threats in their fields. For this study, 138 plots/farms were identified in Europe (112) and China (26). Results show that most widely used promising AMPs in Europe are crop rotation (15%), manuring and composting (15%), and min-till (14%), whereas in China are manuring and composting (18%), residue maintenance (18%), and integrated pest and disease management (12%). In Europe, soil erosion is the main threat in agricultural Mediterranean areas, while soil-borne pests and diseases are more frequent in the SSAs from France and the Netherlands. In China, soil erosion, SOM decline, compaction, and poor soil structure are among the main farmers’ concerns. This research provides relevant information for policy-makers and the development of strategies to support and promote agricultural management practices with benefits for soil quality.